Mental imagery, product involvement and presence at virtual reality supermarket - Loureiro, S. M. C. (2022)
Virtual Reality (VR) is a technology that creates fully immersive and virtual experiences and have been used to create virtual supermarkets and explore consumer behaviour on such alternate reality. The current study uses a VR scenario to analyse the effects of mental imagery, product involvement and presence on customer’s emotions and on the customers purchase intention, during a virtual shopping experience. The proposed model was tested with 108 participants in the laundry detergent category on a VR scenario. Findings reveal that on a virtual setting, mental imagery has the most significant impact on emotions, whereas presence has a strong influence on the purchase decision. Yet product involvement has any effect only on emotions. Moreover, the obsession for laundry products highly decreased the effect of product involvement on purchase intention.